Clinical profile and surgical management of primary vaginal hydrocele: our experience in a rural India - Ahmed, Mohd Hamid Shafique; S., Bankar S.; S., Gosavi V.; B., Dalavi S.; D., Gurav P. (International Surgery Journal, 2017)
Background: Hydrocele is one of the commonest diseases occurring worldwide. Since olden days surgical procedures have been described for the treatment of hydrocele. Aim of the study was to analyse the clinical profile, diagnosis and surgical management of primary vaginal hydrocele in adults (>12 years) Methods: A prospective study of 60 male patients of age range of more than 12 years with a history of scrotal swellings were studied for their clinical profiles, diagnosis and management. The study was carried out in Government Medical College, Miraj, Maharashtra, India from November 2010 to November 2012. In the present study Jaboulay's Procedure was performed on 48 patients and Lord's Procedure was performed on 12 patients. Results: The data was collected and results were analysed. Post-operatively about 1.6% of patients developed hematoma, 5% developed wound infection, 21.66% of the patients developed skin oedema and only 1 patient i.e 1.6 % had recurrence over a period of 2 years of follow up. Out of the total 60 patients,12 patients who underwent Lord's plication 8.33%,0%,0% developed skin oedema, hematoma and wound infection respectively as compared to 25%,2.08%,6.25% in the remaining 48 patients who underwent Jaboulay's procedure, respectively. Conclusions: These two surgical procedures were very safe, easy to perform and economical and associated with minimal recurrence. Lord's procedure has lesser incidence of post-operative complications as compared to Jaboulay's procedure.